# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = \cot \left (x \right ) \cot \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\cot \left (x \right ) \cot \left (y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right ) \left (\csc \left (y\right )-\cot \left (y\right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \tan \left (x \right ) \cot \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\tan \left (x \right ) \cot \left (y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\sin \left (2 x \right ) \csc \left (2 y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \tan \left (x \right ) \left (\tan \left (y\right )+\sec \left (x \right ) \sec \left (y\right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x \right ) \sec \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sec \left (x \right )^{2} \sec \left (y\right )^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a +b \sin \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1+\cos \left (x \right ) \sin \left (y\right )\right ) \tan \left (y\right )
\] |
✓ |
✗ |
|
\[
{}y^{\prime }+\csc \left (2 x \right ) \sin \left (2 y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+f \left (x \right )+g \left (x \right ) \tan \left (y\right ) = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = \sqrt {a +b \cos \left (y\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{y}+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x +y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x} \left (a +b \,{\mathrm e}^{-y}\right )
\] |
✓ |
✓ |
|
\[
{}y \ln \left (x \right ) \ln \left (y\right )+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{m -1} y^{1-n} f \left (a \,x^{m}+b y^{n}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a f \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = f \left (a +b x +c y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = f \left (x \right ) g \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sec \left (x \right )^{2}+y \sec \left (x \right ) \operatorname {Csx} \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime } = 2 \sin \left (y\right )^{2} \tan \left (y\right )-x \sin \left (2 y\right )
\] |
✓ |
✗ |
|
\[
{}2 y^{\prime }+a x = \sqrt {a^{2} x^{2}-4 b \,x^{2}-4 c y}
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime } = x +\sqrt {x^{2}-3 y}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sqrt {a^{2}-x^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+x +y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+x^{2}-y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x^{3}-y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 1+x^{3}+y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x^{m}+y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x \sin \left (x \right )-y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x^{2} \sin \left (x \right )+y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x^{n} \ln \left (x \right )-y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sin \left (x \right )-2 y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = a y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 1+x +a y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = a x +b y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = a \,x^{2}+b y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = a +b \,x^{n}+c y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2+\left (3-x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+x +\left (a x +2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\left (b x +a \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x^{3}+\left (-2 x^{2}+1\right ) y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = a x -\left (-b \,x^{2}+1\right ) y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+x +\left (-a \,x^{2}+2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+x^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x^{2}+y \left (1+y\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y+y^{2} = x^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = a +b y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = a \,x^{2}+y+b y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = a \,x^{2 n}+\left (n +b y\right ) y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = a \,x^{n}+b y+c y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = k +a \,x^{n}+b y+c y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+a +x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\left (1-x y\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \left (1-x y\right ) y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \left (x y+1\right ) y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = a \,x^{3} \left (1-x y\right ) y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x^{3}+\left (2 x^{2}+1\right ) y+x y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y \left (2 x y+1\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+b x +\left (2+a x y\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\operatorname {a0} +\operatorname {a1} x +\left (\operatorname {a2} +\operatorname {a3} x y\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+a \,x^{2} y^{2}+2 y = b
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+x^{m}+\frac {\left (n -m \right ) y}{2}+x^{n} y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\left (a +b \,x^{n} y\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = a \,x^{m}-b y-c \,x^{n} y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 x -y+a \,x^{n} \left (x -y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\left (1-a y \ln \left (x \right )\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+\left (x^{2}-y^{2}\right ) f \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y \left (1+y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y \left (1-x y^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = a \left (x^{2}+1\right ) y^{3}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = a y+b \left (x^{2}+1\right ) y^{3}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = a \,x^{2 k} y^{k}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 4 y-4 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = \sqrt {1+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+\sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+\sqrt {x^{2}-y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+x \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y-x \left (x -y\right ) \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+a \sqrt {y^{2}+b^{2} x^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\left (\sin \left (y\right )-3 x^{2} \cos \left (y\right )\right ) \cos \left (y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+x -y+x \cos \left (\frac {y}{x}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y-x \cos \left (\frac {y}{x}\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \left (-2 x^{2}+1\right ) \cot \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y-\cot \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y+2 x \sec \left (x y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y+x \sec \left (\frac {y}{x}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+x \sec \left (\frac {y}{x}\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sin \left (x -y\right )
\] |
✗ |
✗ |
|
\[
{}x y^{\prime } = y+\sin \left (\frac {y}{x}\right ) x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\tan \left (y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+x +\tan \left (x +y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y-x \tan \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \left (1+y^{2}\right ) \left (x^{2}+\arctan \left (y\right )\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+x \,{\mathrm e}^{\frac {y}{x}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x +y+x \,{\mathrm e}^{\frac {y}{x}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y \ln \left (y\right )
\] |
✓ |
✓ |
|